Design of Fuzzy Logic Controller for Inductor Based Cell Balancing in Battery Management System - Hartono Hartono; Edi Leksono (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2023)
Lithium-ion batteries are a popular energy storage used in various applications including electronic devices, electric vehicles, renewable energy systems, and microgrids. The limitations in capacity and voltage of individual battery cells necessitate arranging them in series and parallel configurations to meet the energy demands of the system. However, connecting cells in series can potentially lead to charge imbalance among cells, resulting in reduced battery pack capacity and triggering safety concerns. Numerous topologies and control methods for battery cell balancing systems have been explored in previous research. In this study, two fuzzy logic controllers with different membership function shapes are designed to drive the duty cycle of PWM signals for inductor-based cell to cell balancing. Based on simulation results, the designed controllers demonstrate good performance compared to conventional methods.